Importance of periodontal ligament thickness - Cuoghi, Osmar Aparecido [UNESP]; Tondelli, Pedro Marcelo; Aiello, Carlos Alberto; Mendonça, Marcos Rogério de [UNESP]; da Costa, Silvano Cesar (FapUNIFESP (SciELO), 2013)
This study evaluated whether periodontal ligament (PL) thickness varied with root size and examined the possible influence of this variation on orthodontic mechanics. Measurements were taken of the maxillary left first molar in 54 male Wistar rats. Mean mesial and distal PL thicknesses were compared between the intermediate buccal and mesiobuccal roots using paired Student's t-tests with a 5% significance level. Mean values differed significantly between roots (p < 2.2 × 10-16). PL thickness in rats is directly proportional to root dimensions.
Keywords: Periodontal ligament; Rats; Tooth movement; Tooth root; animal; biomechanics; histology; male; odontometry; organ size; periodontal disease; periodontal ligament; rat; surface property; tooth root; Wistar rat; Animals; Biomechanics; Male; Odontometry; Organ Size; Periodontal Ligament; Rats, Wistar; Surface Properties; Tooth Movement; Tooth Root